Do differences in clinical symptoms and referral patterns contribute to the gender gap in bladder cancer?. (15th January 2013) - Henning, Armin; Wehrberger, Marlies; Madersbacher, Stephan; Pycha, Armin; Martini, Thomas; Comploj, Evi; Jeschke, Klaus; Tripolt, Christian; Rauchenwald, Michael
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Urothelial carcinoma of the bladder (UCB) is more prevalent in men than women; however, in women the tumour stage is generally more advanced at the time of the diagnosis and the prognosis is worse. Possible explanations include anatomical, genetic and socio‐economic factors. The study shows that clinical symptoms before the first‐time diagnosis of UCB did not differ between the sexes, while primary care and referral patterns did. Women were more likely to receive symptomatic treatment or therapies for alleged UTIs without further investigation or referral to urological evaluation. The study highlights the fact that there may be a diagnostic delay in women which could contribute to the gender‐dependent disparities in stage distribution and prognosis of UCB. Objective To evaluate gender‐dependent disparities regarding clinical symptoms, referral patterns or treatments before diagnosis of urothelial carcinoma of the bladder (UCB). Patients and Methods A consecutive series of patients with newly diagnosed UCB completed a questionnaire at the time of admission for elective transurethral resection of a bladder tumour (TURBT). The questionnaire surveyed the presence of haematuria, dysuria, urgency and bladder pain as well as the number of consultations and treatments before urological evaluation. Tumour characteristics, clinical symptoms, treatments and referrals were compared between men and women in the patient series. Results In men (n = 130) the distribution of tumour stages was pTa 62.3%, pT1 23.1% and pT ≥ 2 12.3%. The respective percentages in women (n = 38) were pTa 57.9%, pT1 23.7% and pT ≥ 2 18.4% (P > 0.05). The prevalence of clinical symptoms in men vs women was as follows: gross haematuria 65 vs 68%, dysuria 32 vs 44%, urgency 61 vs 47%, and nocturia 57 vs 66%, respectively (P > 0.05). A total of 78% of men vs 55% of women directly consulted a urologist (P < 0.05). Symptomatic treatment for voiding disorders/pain was given without further evaluation to 19% of men vs 47% of women 1 year before the diagnosis of UCB (P < 0.05). A total of 3.8% of men vs 15.8% of women received three or more treatments for urinary tract infections (UTIs) within the same time period (P < 0.05). Conclusions In the present study there were no gender‐related differences in clinical symptoms of UCB, but women were more likely to be treated for voiding complaints or alleged UTIs without further evaluation or referral to urology than men. Gender‐dependent disparities in referral patterns exist and might delay definitive diagnosis of UCB in women.